Landscape patterns of carbon fluxes in natural and disturbed ice-wedge-polygon tundra - Anja Kade; Donald A. Walker; Martha K. Raynolds; Amy L. Breen; Olivia M. Hobgood (Arctic, Antarctic, and Alpine Research)
The degradation of ice-rich permafrost ecosystems due to climate change and infrastructure development strongly impacts carbon exchange dynamics in tundra landscapes. This study investigates the effects of surficial geology and infrastructure disturbances from road dust and flooding on vegetation and trace gas fluxes in polygonal ice-wedge tundra in arctic Alaska. We compared CO2 and CH4 fluxes from closed-chamber measurements at common landform elements (polygon centers, troughs, and rims) at a natural site and a disturbed site within the Prudhoe Bay Oil Field. Relationships among environmental parameters, plant species composition, and trace gas fluxes were assessed through nonmetric multidimensional scaling. Map extrapolations showed spatial variations in midsummer landscape-level ecosystem productivity and CH4 efflux at the various geologic landforms. Highest carbon uptake occurred in ice-rich drained thaw lake basins with aquatic, graminoid-dominated polygon troughs. In contrast, wet, featureless areas associated with more recently drained, ice-poor thaw lake basins showed a net carbon loss even during summer. The damming effect of road infrastructure led to deeply flooded, minimally vegetated troughs with low ecosystem respiration and high CH4 fluxes close to the road. This work highlights the importance of the complex interactions among surficial geology, landform elements, vegetation type, and disturbance factors in understanding carbon exchange dynamics in ice-rich permafrost environments.